Bilevel programming approach for the quantitative analysis of renewable portfolio standards considering the electricity market. (15th January 2023) - Kwag, Kyuhyeong; Shin, Hansol; Oh, Hyobin; Yun, Sangmin; Kim, Tae Hyun; Hwang, Pyeong-Ik; Kim, Wook
Abstract: Many countries have introduced renewable portfolio standard (RPS) with market systems that allow transactions of renewable energy certificates (RECs) to foster investment in renewable energy (RE). The main objective of this study is to estimate long-term REC prices based on marginal-cost pricing and analyze the RPS system quantitatively. In the proposed method, a mathematical model is constructed as bilevel programming that considers the REC and electricity markets simultaneously, and the KKT conditions are used to solve the nonlinearity of the constructed model. The proposed method has the following advantages: (1) it determines the optimal capacity of RE to implement the RPS system, (2) it derives the long-term marginal cost of the REC market, and (3) it can be used to perform quantitative analyses of the RPS system. Simulation studies were performed in South Korea, and the results indicated that solar photovoltaic accounted for a major portion of the new investment. The marginal cost of the REC market and the impact of the RPS systems on retail electricity prices are estimated to be USD 14.01/REC and USD 4.59/MWh in 2031, respectively (in 2021 USD). Our study provides appropriate price signals to the market participants and serves as a reference for policymakers. Highlights: A bilevel model considering REC and electricity markets simultaneously was proposed. The impact of the RPS system on Korean markets was assessed using the proposed model. A total of 79, 287 MW of RE should be constructed by 2031 to meet the RPS target. The marginal cost of the REC market is estimated to decrease by 12.2% annually. The impact of RPS on retail electricity price is estimated to be USD4.59/MWh in 2031.